If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + -2) = -1.5 Reorder the terms: 3x(-2 + x) = -1.5 (-2 * 3x + x * 3x) = -1.5 (-6x + 3x2) = -1.5 Solving -6x + 3x2 = -1.5 Solving for variable 'x'. Reorder the terms: 1.5 + -6x + 3x2 = -1.5 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 1.5 + -6x + 3x2 = 0.0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 0.5 + -2x + x2 = 0.0 Move the constant term to the right: Add '-0.5' to each side of the equation. 0.5 + -2x + -0.5 + x2 = 0.0 + -0.5 Reorder the terms: 0.5 + -0.5 + -2x + x2 = 0.0 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + -2x + x2 = 0.0 + -0.5 -2x + x2 = 0.0 + -0.5 Combine like terms: 0.0 + -0.5 = -0.5 -2x + x2 = -0.5 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = -0.5 + 1 Reorder the terms: 1 + -2x + x2 = -0.5 + 1 Combine like terms: -0.5 + 1 = 0.5 1 + -2x + x2 = 0.5 Factor a perfect square on the left side: (x + -1)(x + -1) = 0.5 Calculate the square root of the right side: 0.707106781 Break this problem into two subproblems by setting (x + -1) equal to 0.707106781 and -0.707106781.Subproblem 1
x + -1 = 0.707106781 Simplifying x + -1 = 0.707106781 Reorder the terms: -1 + x = 0.707106781 Solving -1 + x = 0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0.707106781 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0.707106781 + 1 x = 0.707106781 + 1 Combine like terms: 0.707106781 + 1 = 1.707106781 x = 1.707106781 Simplifying x = 1.707106781Subproblem 2
x + -1 = -0.707106781 Simplifying x + -1 = -0.707106781 Reorder the terms: -1 + x = -0.707106781 Solving -1 + x = -0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -0.707106781 + 1 Combine like terms: -1 + 1 = 0 0 + x = -0.707106781 + 1 x = -0.707106781 + 1 Combine like terms: -0.707106781 + 1 = 0.292893219 x = 0.292893219 Simplifying x = 0.292893219Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.707106781, 0.292893219}
| 13b+7b= | | 4w+2=4w+7 | | 2x+8-3=11+11+11 | | w*3=7 | | 29r+4=28+1r | | (w/(2w-3))=4/w | | 4x^2+24x+4y^2+4y-363=0 | | 6x-39=3x+42+11x | | 5.98t=1.4t-13.53 | | 2r(x-3)=15 | | a=6-2b | | 6x+9-8(x+1)=3x+5 | | -2=-(n-a) | | x*4=15 | | 5x+13=5(2+2x)-8x | | (x+3)2=-3+k | | (3u+2)(7+u)=0 | | 7(y+6)+7y=9 | | 29x^2-24x-1.44=0 | | 4(x+1.48)=3x | | 5w+3w=20 | | 3y-5=12 | | .3x^2-.7x-4.0=0 | | 15+3m=7m+3 | | -2.29x^2-.24x-.0144=0 | | 32x+17y=196 | | S-1.8x=6.4 | | x^2+12x+100=y | | -6(6x+2)=4x-12 | | (2x-1)(x+3)=15 | | -4(t+1)-t-14=-5(t+5)+7 | | 3x(6+x)=24 |